Encyclia cajalbanensis (Orchidaceae), una especie nueva de la flora cubana - Mújica Benítez, Ernesto; Bocourt Vigil, José; Pupulin, Franco (Lankesteriana: International Journal on Orchidology, 2015)
A new species of the genus Encyclia, endemic to the Cajálbana plateau in Cuba, is described and illustrated. Encyclia cajalbanensis is similar to E. fucata, from which it differs by the greater size of the plant and the much larger lip, provided with a reniform-suborbicular midlobe.